Physical, mechanical and environmental properties of fired clay bricks incorporated with palm oil mill waste - Sarani, Noor Amira (2019)
The growth of the oil palm industry in Malaysia has generated a significant amount of palm oil mill waste (POMW) causing waste disposal problems. Due to operational challenges and expensive operational cost, POMW is potentially incorporated into fired clay brick owing to high lignocellulosic characteristics. Therefore, this study aims to investigate the physical, mechanical and environmental properties of POMW such as palm kernel shell (PKS), palm oil fuel ash (POFA), palm fibre (PF) and empty fruit bunch (EFB) as a replacement material for brick making. In this study, bricks were manufactured with 0, 1, 5 and 10% of POMW and fired at 1050°C (heating rates at 1, 3 and 5°C/min). The results showed that bricks with 5% of POMW and fired at 1°C/min are significant to reach equilibrium between positive (decrease of weight and increase of porosity) and negative (increase of water absorption and decrease of mechanical resistance) effects. The leaching of Toxicity Characteristic Leaching Procedure (TCLP) and Synthetic Precipitation Leaching Procedure (SPLP) tests revealed that all bricks complied with the United States of Environmental Protection Agency (USEPA) and World Health Organization (WHO) regulation due to the effectiveness of thermal treatment encapsulated heavy metals within the brick matrix by forming lead ferrite, chromia, gahnite and jacobsite. Meanwhile, the incorporation 5% of POMW (1°C/min) into fired clay brick positively contribute to the energy saving from 5.5% to 13.4% due to the embodied energy stored in POMW released during the firing process and thus generates secondary heat input to the furnace. In the meantime, the estimated total emission (ETE) revealed that higher heating rates significantly emit lower gases during firing period. However, lower heating rate (1°C/min) should be considered to attain excellent properties of brick. As a conclusion, incorporation 5% of POMW (1°C/min) is capable of improving better physical and mechanical properties, complies with the environmental standard as well as providing an alternative new disposal method for the wastes as one of the green technology in construction industry as stated in the Government’s Eleven Malaysia Plan (RMK-11).